Seriously stressed. - Films for the Humanities (Firm) (Princeton, NJ : Films for the Humanities & Sciences, 2006)
The pace of life has greatly increased, and the escalation of chronic stress is costing people their health, relationships, and careers. In this program, an immunologist, a psychiatrist, and a mental skills coach lay bare the symptoms of chronic stress, the negative impact on the body of continual exposure to adrenalin and cortisol, and biological and psychological factors that influence vulnerability to overstressing. The fight/flight/freeze response function and the stress/resistance/recovery curve are also addressed. Case studies include an IBM executive, an administrative assistant, and a crime scene videographer.
Keywords: Stress management; Stress (Psychology)